Acute-Phase Serum Amyloid A May Predict Microvascular Invasion and Early Tumor Recurrence in Patients with Hepatitis B Virus-Related Hepatocellular Carcinoma Undergoing Liver Resection. Issue 6 (1st June 2022) - Guo, Xinggang; Zhang, Wenli; Du, Jin; Tao, Rongsuo; Dong, Wei; Huang, Jian; Zhang, Jinmin; Pan, Zeya; Zhou, Weiping; Zhu, Xiuli; Liu, Hui; Liu, Fuchen
Abstract: Objective: To elucidate the impact of acute-phase protein serum amyloid A (aSAA) on microvascular invasion (MVI) and early recurrence in hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Methods: HBV-related HCC patients ( n = 192) undergoing liver resection were included in the study. The protein levels of aSAA were analyzed by immunohistochemical staining in 172 tumor specimens, and further detected via western blotting in HCC and their corresponding portal vein tumor thrombus (PVTT) ( n = 20). Cox and logit regression analysis was performed. Exploratory subgroup analysis was used to balance the potential confounders. Results: HBV-related HCC patients with high aSAA levels tended to have high HBV-DNA loads. Logit and Cox regression analyses revealed high expression of aSAA is an independent risk factor not only for MVI (OR 5.384, 95% CI 2.286–13.301, P < 0.001) but also for early recurrence (HR 6.040, 95% CI 1.970–18.540, P = 0.002), overall recurrence (HR 3.720, 95% CI 2.140–6.450, P < 0.001), and overall survival (HR 4.15, 95% CI 2.380–7.230, P < 0.001). Subgroup analysis showed that the effects of aSAA were consistent across all subgroups examined. Additionally, the aSAA protein level was significantly higher in PVTT than that in its corresponding tumor specimen. A high HBV-DNA level and large tumor size were the independent risk factors for early HCC recurrence in patients with high levels of aSAA. Conclusions: High expression of aSAA was an independent risk factor for MVI and early tumor recurrence in HBV-related HCC patients after liver resection. The aSAA protein level could thus be a promising biomarker for predicting MVI and early recurrence in these patients.